2022
DOI: 10.1002/app.52169
|View full text |Cite
|
Sign up to set email alerts
|

Advance modification of polyacrylonitrile nanofibers for enhanced removal of hexavalent chromium from water

Abstract: Hexavalent chromium [Cr(VI)] is a known carcinogenic and mutagenic heavy metal. Its level in drinking water is regulated worldwide to protect public health. This study presents a novel chemical method to modify the polyacrylonitrile (PAN) nanofibers for efficient Cr(VI) removal from water. The PAN nanofibers with an average diameter of 165 nm are produced using the electrospinning technique. Through a 2-step chemical modification process, the amidine polyacrylonitrile (APAN) nanofibers are synthesized by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Eqn (5) shows the functional relationship between the transmittance and signal wavelength. The effective wavelength range of the collected signal is 340-1100 nm.…”
Section: Theoretical Model Of Mlsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eqn (5) shows the functional relationship between the transmittance and signal wavelength. The effective wavelength range of the collected signal is 340-1100 nm.…”
Section: Theoretical Model Of Mlsmentioning
confidence: 99%
“…The effective wavelength range of the collected signal is 340-1100 nm. Combined with the measurement conditions, the xed measurement values can be substituted into eqn (4) and (5). Therefore, the curve relationship between the total transmittance and wavelength can be obtained as shown in Fig.…”
Section: Theoretical Model Of Mlsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PVC membrane suffers from the membrane fouling during filtration because of its intrinsic hydrophobicity, resulting in a sharp decrease in permeate flux 10 . Numerous strategies have been implemented to increase the hydrophilicity of membrane surface including surface coating, 11,12 surface grafting, 13,14 and blending technique 15,16 . Zhou et al 17 investigated the PVC/poly(vinyl chloride‐ co ‐poly(ethylene glycol) methyl ether methacrylate) (poly(VC‐ co ‐PEGMA)) blending membrane and found that the coverage of PEGMA component on the membrane surface increased the surface pore sizes, hydrophilicity and antifouling properties.…”
Section: Introductionmentioning
confidence: 99%
“…10 Numerous strategies have been implemented to increase the hydrophilicity of membrane surface including surface coating, 11,12 surface grafting, 13,14 and blending technique. 15,16 Zhou et al 17 investigated the PVC/poly(vinyl chloride-co-poly(ethylene glycol) methyl ether methacrylate) (poly(VC-co-PEGMA)) blending membrane and found that the coverage of PEGMA component on the membrane surface increased the surface pore sizes, hydrophilicity and antifouling properties. Liu et al 18 demonstrated a polyamide thin-film composite membrane with highly antifouling properties.…”
Section: Introductionmentioning
confidence: 99%